Medications and medical costs for diabetes patients with or without chronic respiratory disease in Beijing, China: A retrospective study - Qiao, Jingtao; Tan, Zheng; Xu, Xiaomao; Zhou, Yan; Wang, Weihao; Luo, Jingyi; Fan, Jingwen; Pan, Qi; Guo, Lixin (Frontiers in Endocrinology, 2022)
Aims: The cost of drug regimens prescribed to Chinese patients has not been evaluated. This study aim to evaluate the medical costs and hypoglycemic agents for diabetes mellitus patients with or without chronic respiratory disease in Beijing. Meanwhile, to investigate the changes in the costs and number of antidiabetic medications used for diabetes patients with chronic respiratory disease from 2016 to 2018. Methods: This observational, retrospective study included diabetes patients with outpatient medication records from Beijing Medical Insurance between 2016 and 2018. The medications including hypoglycemic and non-hypoglycemic drugs, insulin dosage, comorbidities, diabetes-related complications, treatment strategies and annual medical costs were recorded. Results: This study included 2853036 diabetes patients from 2016 to 2018. About 18.95-20.53% of patients with chronic respiratory disease were predominantly distributed among those aged 45-84 years old (88.7-89.1%). diabetes patients with chronic respiratory disease used more medications (4.48 ± 2.41 vs. 3.76 ± 2.33) and total annual drug costs (¥12286 ± 10385 vs. ¥9700 ± 9202) to treat more comorbidities (2.52 ± 1.53 vs. 2.05 ± 1.85) than those without chronic respiratory disease (p < 0.0001, respectively). From 2016 to 2018, diabetes patients with chronic respiratory disease had a 4.2% increase in medication, a 1.9% decrease in comorbidities, and a 5.4% decrease in total annual drug costs. Conclusions: In summary, diabetes patients with chronic respiratory disease had more comorbidities, required more hypoglycemic drugs, and had higher medical costs. During 2016-2018, diabetes patients with chronic respiratory disease used more medications and spent less money on medical care.